2016
DOI: 10.1038/srep35585
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Complementary Logic Circuits with Ambipolar Organic Transistors

Abstract: Ambipolar organic electronics offer great potential for simple and low-cost fabrication of complementary logic circuits on large-area and mechanically flexible substrates. Ambipolar transistors are ideal candidates for the simple and low-cost development of complementary logic circuits since they can operate as n-type and p-type transistors. Nevertheless, the experimental demonstration of ambipolar organic complementary circuits is limited to inverters. The control of the transistor polarity is crucial for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…CMOS inverters are basic units in complementary circuits and composed of p‐ and n‐type transistors with symmetric threshold voltages as well as analogous response speed . In the course of work, the two pairs of gate and drain electrodes of p‐ and n‐type transistors are linked together and function as input and output terminals.…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…CMOS inverters are basic units in complementary circuits and composed of p‐ and n‐type transistors with symmetric threshold voltages as well as analogous response speed . In the course of work, the two pairs of gate and drain electrodes of p‐ and n‐type transistors are linked together and function as input and output terminals.…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…Another design approach is implementing a split‐gate ambipolar OTFT . In a split gate device, the polarity of the transistor can be controlled using an additional gate electrode.…”
Section: Comparison Of Split‐gate Devices In Terms Of the Gate Electrmentioning
confidence: 99%
“…Gate bias stress, a shift in threshold voltage under operation, should be negligible in order to realize robust circuits. Unfortunately, previous works on split‐gate ambipolar OTFTs either showed large hysteresis in I – V characteristics or reported only the forward voltage sweep characteristics without investigating the I – V hysteresis ( Table 1 ). The main reason for the observed gate bias stress in previously reported split‐gate ambipolar OTFTs is that previous devices used the bottom‐gate device geometry based on inorganic oxide dielectric layers such as SiO 2 or Al 2 O 3 .…”
Section: Comparison Of Split‐gate Devices In Terms Of the Gate Electrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that electrons can also be mobile in many conjugated polymers if an appropriate gate dielectric, in most cases polymers, is chosen leading to the n-type behaviour [10]. OTFTs which can operate in both p-type and n-type conduction modes (ambipolar behaviour) are ideal candidates for the simple and low-cost development of complementary like circuits [11]. Polymer dielectrics have recently been used as gate dielectrics in OTFTs due to their simple processing via spin-coating or -casting, and easy tuning of surface chemical properties [12].…”
Section: Introductionmentioning
confidence: 99%